Factors Impacting Discharge Destination Following Head and Neck Microvascular Reconstruction. (12th May 2022) - Sweeny, Larissa; Slijepcevic, Allison; Curry, Joseph M.; Philips, Ramez; Bonaventure, Caroline A.; DiLeo, Michael; Luginbuhl, Adam J.; Crawley, Meghan B.; Guice, Kelsie M.; McCreary, Eleanor; Buncke, Michelle; Petrisor, Daniel; et al.
Abstract : Objective: Determine which variables impact postoperative discharge destination following head and neck microvascular free flap reconstruction. Study Design: Retrospective review of prospectively collected databases. Methods: Consecutive patients undergoing head and neck microvascular free flap reconstruction between January 2010 and December 2019 ( n = 1972) were included. Preoperative, operative and postoperative variables were correlated with discharge destination (home, skilled nursing facility [SNF], rehabilitation facility, death). Results: The mean age of patients discharged home was lower (60 SD ± 13, n = 1450) compared to those discharged to an SNF (68 SD ± 14, n = 168) or a rehabilitation facility (71 SD ± 14, n = 200; p < 0.0001). Operative duration greater than 10 h correlated with a higher percentage of patients being discharged to a rehabilitation or SNF (25% vs. 15%; p < 0.001). Patients were less likely to be discharged home if they had a known history of cardiac disease (71% vs. 82%; p < 0.0001). Patients were less likely to be discharged home if they experienced alcohol withdrawal (67% vs. 80%; p = 0.006), thromboembolism (59% vs. 80%; p = 0.001), a pulmonary complication (46% vs. 81%; p < 0.0001), a cardiac complication (46% vs. 80%; p < 0.0001), or a cerebral vascular event (25% vs. 80%; p < 0.0001). There was no correlation between discharge destination and occurrence of postoperative wound infection, salivary fistula, partial tissue necrosis or free flap failure. Thirty‐day readmission rates were similar when stratified by discharge destination. Conclusion: There was no correlation with the anatomic site, free flap donor selection, or free flap survival and discharge destination. Patient age, operative duration and occurrence of a medical complication postoperatively did correlate with discharge destination. Level of Evidence: 4 Laryngoscope, 133:95–104, 2023 Abstract : The objectives of this study are to review preoperative variables and postoperative outcomes to determine correlates for discharge destination following free flap reconstruction of a head and neck defect in the hopes of improving preoperative counseling and preparation leading to better optimization of patient care and expedited discharges. This study uniquely demonstrates that the anatomic site of the reconstruction and surgical indication did not influence discharge placement. This study found increasing age, operative duration greater than 10 h and occurrence of a postoperative medical complication to increase the likelihood of patients requiring admission to a rehabilitation or skilled nursing facility following free flap reconstruction of a head and neck defect.